D’une initiative locale à un essaimage national, l'histoire du développement du maïs en France - AgroBio Périgord (Revue d'ethnoécologie)
For more than 15 years, a group of farmers from Dordogne has been working on the origin, quality and diversity of crops used in organic and sustainable farming systems. This article describes the rising of awareness among Agrobio Périgord farmers and the actions implemented to recover traditional knowledge in evolutionary plant breeding and in self-production of seed saving and integrate them on their farms, in particular for maize. They thus tackle important questions about biodiversity conservation and farmers’ autonomy, as well as savings and the adaptation of crops and practices to their farming methods. Within the “Cultivons la biodiversité en Nouvelle-Aquitaine” program, Agrobio Périgord works on experimentation, plant breeding and recovery of knowledge on peasant seeds.